2017
DOI: 10.1111/cei.12975
|View full text |Cite
|
Sign up to set email alerts
|

Associations of B cell-activating factor (BAFF) and anti-BAFF autoantibodies with disease activity in multi-ethnic Asian systemic lupus erythematosus patients in Singapore

Abstract: To measure the levels of B cell-activating factor (BAFF) and endogenous anti-BAFF autoantibodies in a cohort of multi-ethnic Asian systemic lupus erythematosus (SLE) patients in Singapore, to determine their correlation with disease activity. Serum samples from 121 SLE patients and 24 age- and sex-matched healthy controls were assayed for BAFF and anti-BAFF immunoglobulin (Ig)G antibody levels by enzyme-linked immunosorbent assay (ELISA). The lowest reliable detection limit for anti-BAFF-IgG antibody levels wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“… 5 44 The overexpression of BAFF in SLE is hypothesised to be driven by localised inflammation or B cell activation resulting from inherent immune dysregulation in SLE. 30 45 BAFF levels have also been associated with disease activity 46 and organ damage 47 48 in some but not all cohort studies. 45 Yet, the failure of monoclonal anti-BAFF therapy to dampen disease activity 49 suggests that aberrant BAFF production is a feature rather than a direct cause of lupus disease activity.…”
Section: Discussionmentioning
confidence: 99%
“… 5 44 The overexpression of BAFF in SLE is hypothesised to be driven by localised inflammation or B cell activation resulting from inherent immune dysregulation in SLE. 30 45 BAFF levels have also been associated with disease activity 46 and organ damage 47 48 in some but not all cohort studies. 45 Yet, the failure of monoclonal anti-BAFF therapy to dampen disease activity 49 suggests that aberrant BAFF production is a feature rather than a direct cause of lupus disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a Swiss study of adult SLE patients did not demonstrate an increase in anti-BAFF autoantibody levels or any association with SLE disease activity while serum BAFF-IgG complexes were associated with serological and clinical SLE disease activity [13]. We recently observed elevated levels of anti-BAFF antibodies in the majority of our multi-ethnic Asian SLE patients, which correlated negatively with clinical disease activity, levels of anti-dsDNA antibodies, and serum BAFF, suggesting that they may be immunomodulatory in nature and may serve as a tool in monitoring disease progression [54].…”
Section: Anti-baff Autoantibodies In Slementioning
confidence: 79%
“…Several recent studies have reported raised levels of endogenous anti-BAFF autoantibodies in SLE both in adult [53,54] as well as in pediatric patients [55]. Raised anti-BAFF autoantibody levels were found to correlate with disease activity in pediatric SLE patients [55].…”
Section: Anti-baff Autoantibodies In Slementioning
confidence: 87%
“…Furthermore, the circulating BAFF levels have correlated with disease‐associated antibody levels in SLE, 62,238 rheumatoid arthritis, 74 and Sjogren's syndrome 77 . A negative correlation between the serum level of antibodies to BAFF (anti‐BAFF) and disease activity in SLE has supported the concept of BAFF as a pathogenic factor 240 …”
Section: Baff and April In Diverse Autoimmune Diseasesmentioning
confidence: 99%
“…BAFF has been implicated as a biomarker for disease activity and a pathogenic factor in patients with SLE, 62,70,238‐242 rheumatoid arthritis, 72,74 and Sjogren's syndrome (Table 4). 76,77 The over‐expression of BAFF has been demonstrated by increased serum levels of soluble BAFF in patients with SLE, 62,239‐241 rheumatoid arthritis, 72,74 and Sjogren's syndrome 76,77 and by increased levels of mRNA for BAFF in the leukocytes of patients with active SLE 65,66,238,239 . Furthermore, the circulating BAFF levels have correlated with disease‐associated antibody levels in SLE, 62,238 rheumatoid arthritis, 74 and Sjogren's syndrome 77 .…”
Section: Baff and April In Diverse Autoimmune Diseasesmentioning
confidence: 99%